Presence of mEGFR ctDNA predicts a poor clinical outcome in lung adenocarcinoma. Issue 12 (24th October 2019) - Kim, Taehee; Kim, Eun Young; Lee, Sang Hoon; Kwon, Do Sun; Kim, Arum; Chang, Yoon Soo
Abstract : Background: Circulating tumor DNA (ctDNA) is a biomarker for the selection of target agents in various malignancies. In this study, we examined the effect of ctDNA presence on the response to EGFR‐tyrosine kinase inhibitor (TKI) and on the prognosis in lung adenocarcinoma. Methods: ctDNA of EGFR‐TKI sensitizing mutations (mEGFR), L858R substitution and Exon 19 deletion (E19d) mutation, was evaluated using droplet digital PCR (ddPCR) in 81 patients with lung adenocarcinoma which harbored mEGFR in the corresponding tumor tissues. Results: The study recruited lung cancer patients at various stages, and the sensitivity, specificity, and area under the curve (AUC) of mEGFR ctDNA detection by ddPCR were 40.0%, 88.5%, and 0.68, respectively. It showed higher sensitivity (75.0% vs. 10.0%) and AUC (0.83 vs. 0.49) in the advanced stages of lung adenocarcinoma compared with the early stages and the number of metastases and the fractional abundance of mEGFR ctDNA showed a strong correlation (σ = 0.516; P < 0.001, Spearman correlation test). There was a significantly shorter progression‐free survival and duration of disease control by EGFR‐TKIs in the ctDNA‐positive group than the negative group (14.0 vs. 41.0 months, P = 0.02 and 12.0 vs. 23.0 months, P = 0.02, log‐rank test, respectively). There was a trend for overall survival time to be shorter in patients with mEGFR ctDNA than for patients without mEGFR ctDNA (35.6 vs. 67.1 months, P = 0.06, log‐rank test). Conclusions: These data showed that mEGFR ctDNA detection using ddPCR is useful in the advanced stages and its presence predicted distant metastasis and poor clinical outcome in lung adenocarcinoma.